BASYS-MTB: An integrative structural simulation platform based on adjacency matrices. (April 2020) - Al-Sayegh, Ammar Taher; Noroozinejad Farsangi, Ehsan
Abstract: The objective of this work is to develop and test a new data structure, which takes advantage of the latest programming technology to build interactive structural engineering modeling software that is robust, efficient, portable, modular, expandable, and easy to use. The data structure proposed is composed of a collection of matrices that describe both the geometrical properties and the topological adjacency information of the structural model, as well as the section, material, loading, and fixity attributes of the structural elements. This data structure is dubbed the Adjacency Matrix Data Structure (AMDS). There are eight matrices in the AMDS, each capturing the details of one type of structural entity or attribute: Vertex, Edge, Face, Group, Section, Material, Load, and Fixity. The design of the AMDS allows it to excel in terms of efficiency and speed when used in a matrix-based programming environment, such as MATLAB. The final outcome called "BASYS-MTB " is a structural modeling and visualization MATLAB Toolbox that is a demonstration implementation of the AMDS as the underlying data structure. The toolbox, which can serve as a preprocessor, solver, and postprocessor, employs the object-oriented programming capabilities in MATLAB to create and manipulate numerical and graphical objects. This system offers engineers and researchers with limited programming expertise a structural modeler that can be easily customized to their requirements using their existing knowledge in MATLAB.